Optimization of Ticket Sales for Tehran Azadi stadium with the Approach of Simulating Queuing Systems and MCDM - Ali Jamshidi; Javad Shahlaee; Gholamali Kargar (New Approaches in Sport Sciences)
The purpose of the present study was to optimize and improve the status of ticket sales at Tehran Azadi Stadium and reduce customer waiting times in queues using methods Simulation and Multi-criteria decision making (MCDM). First, using objective observation and time-out, the waiting time for spectators in the ranks of the ticket and presentation and physical examination calculations and then using the simulation software, The entire service process has been simulated from the moment the ticket is purchased until the moment they enter the stadium, and the average waiting time for spectators in the queue for the provision of services is calculated. And then we look at the problems with ticket sales. Also, using interviews with elite and expert people, there are some ways to reduce waiting times for customers in the queue. And each of these views was examined using the simulation software; then scenarios were developed to improve the status quo and then, using multi-criteria decision-making methods, we ranked the scenarios and selected the best scenario.